Assessment of immunological factors in COVID-19 patients treated by convalescent plasma: Immunological factors in COVID-19 by convalescent plasma - Heidari, Mozhdeh; Yaghobi, Ramin; Moghadami, Mohsen; Zand, Farid; Fallahi, Mohammad Javad; Pourfathollah, Ali Akbar; Zarnegar, Golnoush; Salah, Alireza; Soleimanian, Saeedeh; Golshan, Mehdi; Jangjou, Ali; Karimi, Mohammad Hossein (Cellular and Molecular Biology, 2024)
Following the outbreak of COVID-19, several immunotherapy methods were used to modulate the immune responses of patients. In this study, we aimed to evaluate the immune response to COVID-19 in patients receiving convalescent plasma. In this regard, this randomized controlled trial included 30 patients who were divided into two groups according to receiving convalescent plasma or normal control plasma. Samples from both groups were collected on days 0, 1, 3, 5 and 7 after plasma infusion. We measured the expression level of TLR7/8, IRF3/7, CTLA-4, PD-1 and T cell transcription factors by Real-time PCR in the mentioned groups. Thirteen cytokines were also evaluated using flow cytometry method. Results showed that compared to the normal control plasma group, the expression levels of TLR7, 8, IRF3, 7 and PD-1 and CTLA-4, on days 3, 5 and 7 after convalescent plasma infusion, were significantly decreased. On the other hand, Gene expression results showed that the expression levels of Tbet, RORγ3 and Foxp3 on days 3, 5 and 7 after convalescent plasma infusion were significantly increased compared to the normal control plasma group. After convalescent plasma infusion, the viral load was significantly decreased compared to the normal control plasma group. Convalescent plasma infusion also reduced the plasma cytokines levels, including IL-6, IL-10, and IL-4, and enhanced the level of IL-2, IFN- γ and perforin comparing the normal control plasma group. According to the results, the convalescent plasma infusion led to a decrease in the expression of innate immunity receptors and an increase in the expression of transcription factors of adaptive immunity. Therefore, it may be concluded that convalescent plasma infusion can modulate the immune response. To achieve a reliable consequence, further studies are required.